From a sugar beet nematode to problems of food security - K. A. Perevertin; A. O. Sagitov (Российский паразитологический журнал, 2016)
Modern development of systems of land use assumes the solution of problems not only at biological level, but also use geographical, economic, social and even political blocks. On an example of beets heteroderosis attempt an illustration of depth of these interrelations is made. The role of the founder of system researches in this area - prof. T.S. Skarbilovich is emphasized